India's Experience with ICT in the Health Sector: Lessons for sub-Saharan Africa - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
Health systems challenges of northern and eastern India are similar to those in sub-Saharan Africa. Both India and Africa suffer from acute shortage of doctors, most notably specialists, like ophthalmologists, radiologists, cardiologists, oncopathologists and many more. The specialists and their services are concentrated in cities leaving rural areas isolated from their support. In India, around 68% of the population lives in rural areas where there is acute shortage of doctors and health care specialists. In sub-Saharan Africa, on average, there are less than 10 doctors per 100,000 people, and there is not even a single radiologist in 14 countries. India and Africa suffer from high burden of infectious diseases, emerging epidemic of non-communicable diseases, double burden of malnutrition, urbanisation, limited healthcare workforce, shortage of drugs and supplies, weak monitoring and evaluation systems, lack of follow-up care, limited financing mechanisms etc. Aligned with the Sustainable Development Goals (SDGs), India and Africa share a common vision of providing universal health coverage (UHC) to their populations. Both the regions are accelerating in developing healthcare innovations, supported by various factors such as increased use of smartphones, expanding healthcare markets and strong policy initiatives in healthcare. India shares strong historical and ongoing ties with Africa. Some of the past and ongoing joint initiatives in the healthcare sector include Pan African e-Network Project, e-VidyaBharati and e-AarogyaBharati (e-VBAB) Network Project, India-Africa Forum Summits, India Africa Health Sciences Platform, NATHEALTH-Healthcare Federation of India and Africa Healthcare Federation (AHF) Collaboration, Medical Tourism and Vaccine Maitri Initiative. This paper describes India's experience with ICT interventions in the Health sector which could provide valuable lessons for sub-Sahran Africa. Some of the digital health initiatives taken by India include use of telemedicine, mHealth and Artificial Intelligence to deal with COVID-19 situation, mobile telepothalmology services, e-pharmacy, NCG-Vishwam Cancer Care Connect, Electronic Resources in Medicine (ERMED) Consortium, use of Artificial Intelligence for cancer screening and treating diabetic retinopathy, AYUSH GRID, e-Governance in healthcare, Common Service Centre Program, National Digital Wellbeing Platform (MANAS), National Digital Health Mission (NDHM) and National Nutrition Mission. Given that Africa and India share many commonalities, particularly in terms of healthcare challenges, there is considerable practical potential for Africa to learn and adopt from India's digital healthcare interventions. Many of these initiatives could serve as a valuable solution for health problems prevalent in the sub-Sahran Africa region. Sub-Saharan African countries could learn from these initiatives and encourage similar initiatives in their region for improving the delivery of healthcare services.
Keywords: 330; Information and Communications Technology; ICT; Health; India; Africa